1999
DOI: 10.1081/ddc-100102218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plasticizers and Drugs on the Physical-Mechanical Properties of Hydroxypropylcellulose Films Prepared by Hot Melt Extrusion

Abstract: Hydroxypropylcellulose (HPC) films containing drugs or hydrophilic or hydrophobic plasticizers were prepared by a hot melt extrusion process. Polyethylene glycol 8000 (PEG 8000) 2%, triethyl citrate (TEC) 2%, acetyltributyl citrate (ATBC) 2%, and polyethylene glycol 400 (PEG 400) 1% were the plasticizing agents studied. In addition, either hydrocortisone (HC) 1% or chlorpheniramine maleate (CPM) 1% was incorporated into the films as a model drug. The physical-mechanical properties of the films that were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(106 citation statements)
references
References 11 publications
3
101
0
2
Order By: Relevance
“…In order to ensure the adhesion of the enteric coating polymer dispersion, the amount of plasticizer (TEC) was adjusted to manufacturer recommended specifications for enteric coatings (Table 1). Because pharmaceutical acrylic polymers are brittle, fragile and exhibit strong adhesiveness [52], the addition of plasticizers and glidants, such as talc (Table 1), ensures the favorable elasticity of the coatings by decreasing polymer tensile strength [52,53], lowering the film forming temperature without adverse mechanical effects [54][55][56][57][58], and facilitating GI transit through mucosal surfaces by avoiding polymer dispersion agglomeration.…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure the adhesion of the enteric coating polymer dispersion, the amount of plasticizer (TEC) was adjusted to manufacturer recommended specifications for enteric coatings (Table 1). Because pharmaceutical acrylic polymers are brittle, fragile and exhibit strong adhesiveness [52], the addition of plasticizers and glidants, such as talc (Table 1), ensures the favorable elasticity of the coatings by decreasing polymer tensile strength [52,53], lowering the film forming temperature without adverse mechanical effects [54][55][56][57][58], and facilitating GI transit through mucosal surfaces by avoiding polymer dispersion agglomeration.…”
Section: Discussionmentioning
confidence: 99%
“…They found that all the studied plasticizers showed good plasticizing effect, except for PEG 400 which initially showed good effect, but on storage the films became unstable (12). Whereas in the present study, the authors are focusing on screening different polyols as plasticizers at concentration of 10-20% w/w, except for maltitol studied at 20 and 30% w/w concentration.…”
Section: Effect Of Plasticizers On Hme Of Kldmentioning
confidence: 99%
“…Some polymers cannot be extruded without using plasticizers or drug at particular concentration in the formulation, since these polymers produce excessive torque between the screws when extrusion is performed with polymer alone. For example, Repka and coworkers have reported that hydroxypropyl cellulose (HPC) films cannot be extruded without using plasticizers in the formulation (12). Plasticizers are typically ingredients with low molecular weight, either in liquid or solid state.…”
Section: Hme Of Kleptose Linecaps De17mentioning
confidence: 99%
“…Several authors have successfully used HME technology to prepare various dosage forms including tablets, pellets, granules, and films (Zhang et al, 1992;Follonier et al, 1995;Aitken-Nichol et al, 1996;Repka et al, 1999;Young et al, 2002). HME may be used to disperse drugs in a given matrix at the molecular level, thus forming solid solutions.…”
Section: Introductionmentioning
confidence: 99%